The Interpersonal-Psychological Theory of Suicide to Explain Suicidal Risk in Eating Disorders: A Mini-Review - Zeppegno, Patrizia; Calati, Raffaella; Madeddu, Fabio; Gramaglia, Carla (Frontiers in Psychiatry, 2021)
Suicide is a major cause of death in Eating Disorders (EDs) and particularly in anorexia nervosa (AN). The aim of the present mini-review was to summarize the literature focusing on the interpersonal-psychological theory of suicide (IPTS) by Thomas E. Joiner, as applied to explain suicidal risk in EDs. PubMed database was used to search articles focused on IPTS in EDs; 10 studies were eventually included. The majority of the included studies reported data from the same sample, even though the hypotheses and analyses for each study were unique. The investigated suicidal outcomes were suicidal ideation (SI) (40%), non-suicidal self-injury (10%), suicide attempt (40%) and suicide (10%). In ED patients Perceived Burdensomeness (PB) may play an important role, especially regarding SI risk. ED patients may feel like a burden to their close ones, and actually some of the ED symptoms may be an expression of anger and hate against the self. Overall, currently available research has supported some IPTS derived predictions (i.e., ED symptoms may increase PB and thereby SI), but not others (i.e., the elevated suicide rate in AN may be due to higher acquired capability for suicide). Further research on IPTS tenets as well as on other theoretical perspectives and constructs (e.g., interoceptive awareness), hopefully with a longitudinal design and adequate follow-up duration, might allow a more thorough understanding of the complex topic of suicidal behavior in ED patients.